Answer:
im not vary shur
im so sorry but u may be in a hier grade than me
2 which is the height and 15 would be the width.
Answer:
x = 11, -1
Step-by-step explanation:
First, let's identify what the quadratic formula is:
x = [-b ± √(b² - 4(a)(c))] / 2
Our equation is written in standard form:
ax² + bx + c = 0
x² - 10x - 11 = 0
Let's plug in what we know.
x = [-(-10) ± √((-10)² - 4(1)(-11))] / 2
Evaluate the exponent.
x = [-(-10) ± √(100 - 4(1)(-11))] / 2
Simplify the negatives.
x = [10 ± √(100 - 4(1)(-11))] / 2
Multiply.
x = [10 ± √(100 + 44)] / 2
Simplify the parentheses.
x = [10 ± √(144)] / 2
Simplify the radical (√)
x = [10 ± 12] / 2
Evaluate the ±.
x = [10 + 12] / 2
x = [22] / 2
x = 11
or
x = [10 - 12] / 2
x = [-2] / 2
x = -1
Your answers are x = 11, -1
Hope this helps!
Answer:
- <em><u>average yearly salary of an individual whose final degree is a masters:</u></em><u> $ 66 thousand</u>
<u></u>
- average yearly salary of an individual whose final degree is a bachelors:<u> $ 56 thousand</u>
Explanation:
You can set a system of equation using the following steps:
1. Name the variables:
- average yearly salary of an individual whose final degree is a masters: x
- average yearly salary of an individual whose final degree is a bachelors: y
2. Set the equations that relate the variables:
- the average yearly salary of an individual whose final degree is a masters is $46 thousand less than twice that of an individual whose final degree is a bachelors:
equation (1): x = 2y - 46
- combined, two people with each of these educational attainments earn $122 thousand:
equation (2): x + y = 122
3. Solve the system:
- x = 2y - 46 . . . equation (1)
- x + y = 122 . . . equation (2)
Substitute equation (1) into equation (2)
Solve for y:
- y = 56 (this means that the average yearly salary with a bachelors degree is $ 56 thousand).
Subsitute the value on y in equation 1, to find the value of x:
- x = 2y - 46 = 2(56) - 46 = 112 - 46 = 66.
Thus, the average yearly salary of a person with a masters degree is $ 66 thousand.